INVESTIGATIONS OF PHASE AND STRUCTURE TRANSFORMATIONS IN SOLID PROTON CONDUCTORS ON THE BASE OF BARIUM AND STRONTIUM CERATES - Munasbaeva К. К.; Zhotabaev, Zh. R.; Khromushin, I. V.; Aksenova, T. I.; Tuseyev Т. Т.; Beken, R. E. (Recent Contributions to Physics, 2009)
Influence of different factors on structure and properties of barium and strontium cerates have been investigated. It was shown that doped barium and strontium cerates have high phase-structure stability in wide range of temperatures and partial pressures. At the same time the undoped metal oxides, especially ceramic ones, are tended to phase transformations which bring to lattice symmetry changes and oxygen, water and carbon dioxide molecules release from the samples. High temperature reactor irradiation of the oxides brings to significant changes of their structure. Low temperature reactor irradiation calls just quantitative changes in the oxides.